The making of a sustainable food city in Barcelona: insights from the water, energy, and food urban nexus - Moises Covarrubias; Ingrid Boas (Journal of Integrative Environmental Sciences, 2020)
This paper examines the making of urban sustainable food provisioning through the case of Barcelona. Barcelona is seeking to develop a more sustainable food system. It aims to green its municipal food markets by reducing the distances from which the food is sourced from. This has been labelled by the city of Barcelona as “proximity food”. We shed light on how, and to what extent, proximity food contributes to making the city more sustainable. To frame our analysis, we employ concepts from networks and flows as developed in sociology by Manuel Castells. We examine the provisioning processes that proximity food goes through before they enter retail markets. This includes an analysis of connections with urban energy and water flows. This so-called water, energy and food Urban Nexus, which we argue to be a key factor in the greening of urban food systems. This means that sustainability of food is not just determined by physical distances between its provisioning processes per se but by the specific ways in which food flows relate to connections (both physical and social) with energy and water.